2003
DOI: 10.1007/s00441-003-0726-0
|View full text |Cite
|
Sign up to set email alerts
|

Stroma-mediated granulocyte-macrophage colony-stimulating factor (GM-CSF) control of myelopoiesis: spatial organisation of intercellular interactions

Abstract: Granulocyte-macrophage colony-stimulating factor (GM-CSF) is one of the major cytokines involved in control of haemopoiesis both in bone marrow and in extramedullar sites. Its biological activity depends upon the composition and physicochemical properties of the microenvironment provided by the supporting stroma. GM-CSF activity is modulated and controlled by the stromal heparan-sulphate proteoglycans, but their optimal interaction occurs only at low pH. We questioned whether the microenvironment organisation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…The accumulation of MDSCs is believed to be a specific consequence of GM-CSF’s ability to skew hematopoiesis towards myeloid development. Several studies have reported GM-CSF induced myelopoiesis that is consistent with the myeloid-based model of hematopoiesis (48-50). Transgenic expression of GM-CSFR in hematopoietic tissue results in a preferential shift towards myeloid progenitors at the CMP, GMP and MEP stages (51).…”
Section: Cytokine and Cytokine-induced Transcriptional Regulation Of supporting
confidence: 74%
“…The accumulation of MDSCs is believed to be a specific consequence of GM-CSF’s ability to skew hematopoiesis towards myeloid development. Several studies have reported GM-CSF induced myelopoiesis that is consistent with the myeloid-based model of hematopoiesis (48-50). Transgenic expression of GM-CSFR in hematopoietic tissue results in a preferential shift towards myeloid progenitors at the CMP, GMP and MEP stages (51).…”
Section: Cytokine and Cytokine-induced Transcriptional Regulation Of supporting
confidence: 74%
“…We have proposed previously that the negatively charged extracellular microenvironment generated by the accumulation of molecules such as glycolipids, glycoproteins, and proteoglycans in close proximity to the cell membrane (41) would create a local pH gradient with the external face of the membrane being acidic (17). Recent observations have provided experimental support to this hypothesis; the contact points between GM-CSF-dependent murine FDC-P1 cells and the stromal cells that secrete GM-CSF concentrate negative charges from glycolipids containing sialic acid groups, suggesting that the microenvironment where GM-CSF and its high affinity receptor interact is indeed acidic (34). Moreover, ongoing studies show that the GM-CSF receptor co-localizes with gangliosides on the surface of hematopoietic precursor cells.…”
Section: A Inset)mentioning
confidence: 80%
“…Considerable evidence implicates the sulfated GAGs heparan sulfate and heparin in the modulation of the biological activity of GM-CSF (9,10,33,34). However, to date no GAGbinding sites in GM-CSF have been structurally identified.…”
Section: Discussionmentioning
confidence: 99%
“…If GM-CSF undergoes a pH-induced conformational change that allows heparin to bind, as has been suggested [97], this could explain the lack of in vitro binding data. The interaction of haemopoietic cells with supporting stroma leads to an accumulation of sialylated glycoconjugates and proteoglycans at the interface of the two cell types [97,103]. This may produce a local acidic microenvironment that supports the binding of GM-CSF to membrane heparan sulfates.…”
Section: Regulation Of Heparan Sulfate-protein Interactions In the Timentioning
confidence: 97%